Pandemic on the Ship: Emergency Legality and Human Rights Security of the Floating Isolation Policy in Indonesia - Mujib, M. Misbahul; Kurniawan, Shelly; Basuki, Udiyo; Iswantoro, Iswantoro; Arfaizar, Januariansyah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
The COVID-19 pandemic compelled governments worldwide to implement extraordinary measures that tested the boundaries of legality and human rights protection. This study examines makassar’s floating isolation policy an innovative yet controversial public health intervention that repurposed the km umsini  as a quarantine facility during the 2021 surge in infections. The policy drew debate due to its top-down implementation and concerns that s, historically, have been among the fastest environments for infectious disease transmission, including covid-19. Employing a juridical–empirical approach, this research assesses the policy’s conformity with indonesia’s constitutional obligations and international human rights standards, particularly the international covenant on economic, social and cultural rights (icescr) and the international health regulations (IHR 2005). Field data were obtained through semi-structured interviews with health officials, volunteers, supported by documentary and legal analysis. The findings reveal that while the policy effectively reduced hospital overcrowding and community transmission, it operated within a “gray zone of legality” due to the absence of explicit statutory regulation. Using state obligations theory, the human security framework, and emergency law theory, the study demonstrates that legality during crises can be sustained through transparency, proportionality, and participatory governance. It concludes that compassionate legality rooted in respect for human dignity and procedural fairness can transform emergency discretion into a framework of human-centered resilience. Overall, this research enriches global scholar by illustrating how ship can be innovation in pandemic era redefines the relation between law, human rights, and crisis governance.